The High Selectivity of the Cp2ZrHCl Reducing Agent for Imides: A Combined Experimental and Theoretical Study on γ‐Lactam and Isoxazolidinone Derivatives. Issue 1 (21st November 2012) - Lanza, Giuseppe; Chiacchio, Maria A.; Giofrè, Salvatore V.; Romeo, Roberto; Merino, Pedro
Abstract: Selective reductions of semicyclic imides either to hemiaminals ( endo carbonyl reduction) or to aldehydes and amines ( exo carbonyl reduction) in high yields by Schwartz's reagent (Cp2 ZrHCl) are reported. Mechanistic aspects of these reactions have been investigated at the DFT ab initio level with consideration of implicit solvent effects and thermal and pressure corrections to 298 K/1 atm. The reactions proceed from the reagents to very stable final Zr‐oxo intermediates through the formation of σ complexes and subsequent four‐center transition state structures (1, 2‐migratory insertion). The energetic barriers for the insertion steps depend strongly on the natures of the ancillary groups at the reducing carbonyl groups. N ‐Carbamoyl groups are reduced to hemiaminals whereas N ‐acyl groups react at the exo carbonyl groups. The absence of the second carbonyl group in the simple N ‐methyl‐2‐pyrrolidone (less oxidized system) strongly reduces the thermodynamic drive for the formation of the metallocene oxo intermediate and allows an explanation of the remarkable chemoselectivity of the hydrozirconation. The zirconocene‐oxo intermediates hydrolyze quickly throughout an ionic mechanism in which water molecules strongly assist the process by stabilizing ion pair separation. The computational results are consistent with a large set of experimental data on reduction of γ‐lactam and isoxazolidinone derivatives under mild conditions. They provide a way to explain and predict the relative importance of the two competitive endo / exo reduction channels of semicyclic imides by considering the electronic and steric features of substituents. Abstract : Semicyclic imides such as γ‐lactam and isoxazolidinone derivatives are efficiently and selectivity reduced by the Cp2 ZrHCl agent. The energetic reaction pathways for endo and exo attack, computed at the DFT level including thermal effects, allow an exhaustive interpretation of current and previously reported experimental data.